The Current State Of Development Of Small Business And Private Entrepreneurship In Industry (Eurasian Journal of History, Geography and Economics, 2025)
This article analyzes the current state of development of small business and private entrepreneurship in the industrial sector of Uzbekistan. It highlights the role and significance of small enterprises in the national economy, their contribution to industrial output, job creation, and the enhancement of export potential. The paper also examines government policies aimed at supporting entrepreneurial activity in the industrial sector, existing challenges, and possible solutions.